Pendekatan Sufistik Dalam Pemahaman Hadis Menurut Syekh Muhammad Nafis Al-Banjari Di Kitab Al-Durr Al-Nafis - Hanafi, Hanafi; Nirwana, Dzikri (Institut Agama Islam Sumatera Barat Pariaman, 2024)
This article aims to explore the method of understanding hadith employed by the Banjar scholar, Sheikh Muhammad Nafis al-Banjari (1735–1812 CE), in his renowned work, al-Durr al-Nafis, which is known for its Sufi approach. The study focuses on key concepts such as tawhid al-af’al (the oneness of actions), tawhid al-asma (the oneness of names), tawhid al-shifat (the oneness of attributes), and tawhid al-zat (the oneness of essence). These central themes are rooted in the texts of the Qur'an and hadith, which are interpreted using a Sufi approach. This approach emphasizes intuitive insight derived from the purification of the heart, often prioritizing esoteric meanings over literal interpretations. However, Sufi interpretations are frequently debated, as they are perceived to neglect the literal meanings of hadith. This study employs a qualitative analytical method to describe and analyze this approach, drawing conclusions based on the issues discussed. The findings reveal that Sheikh Nafis’s Sufi-based method of understanding hadith does not always contradict the textual meanings of the hadith. In fact, in several instances, Sheikh Nafis adopts a textual understanding consistent with the methodology of traditional hadith scholars. This research offers new insights into the flexibility of the Sufi method in interpreting hadith and its contribution to the development of hadith exegesis among Banjar scholars.